PERANAN KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA RIAU DALAM PENGAWASAN DAN PENINDAKAN KEIMIGRASIAN TERHADAP ORANG ASING DI PEKANBARU (STUDI KASUS DI KANTOR WILYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA RIAU - Rahmad Salim; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The Ministry of Justice and Human Rights of the Republic of Indonesia is the implementing element of the government which is under and responsible to the President. The Directorate General of Immigration is a structural part of the ministry of justice and human rights that has the main duty of formulating and implementing technical policies and standardization in the field of immigration. The purpose of writing this thesis is; First, State authority of the Regional Office of the Ministry of Justice and Human Rights of Riau in the supervision and enforcement of immigration against foreigners in Pekanbaru. Second; Knowing the supervision of the Regional Office of the Ministry of Justice and Human Rights of Riau in the supervision and enforcement of immigration against foreigners in Pekanbaru.This type of research can be classified into a type of Sociological study. This research is conducted by researching directly to the field and reviewing library materials or secondary data in the form of legislation and books written by lawyers related to research titles, articles, journals and various other sources. The data source used is secondary data source. Secondary data is divided into three types, namely: primary legal materials, secondary legal materials and tertiary legal materials, data collection techniques in this study used interview methods and literature review.From the results of research problems there are two main things that can be concluded. First, the authority of the Regional Office of the Ministry of Justice and Human Rights of Riau in the implementation of supervision and enforcement of immigration against foreigners in Pekanbaru as Coordinator in coordinating, planning, controlling activities of supervisory activities and immigration actions against foreigners, supervisory and supervisory actions for immigration Foreign, law enforcement in the field of immigration. Second, Supervision of Regional Office of the Ministry of Justice and Human Rights of Riau in the implementation of supervision and enforcement of immigration to foreigners in Pekanbaru is to coordinate, control, and supervise technical activities. Supervision and enforcement of immigration by the Immigration Office in accordance with its working area in the Regency and City. All activities of the Immigration Office in carrying out supervision and action against foreigners are supervised and controlled by the Regional Office of the Ministry of Justice and Human Rights of Riau. The results of these activities are reported to the Regional Office of the Ministry of Justice and Human Rights of Riau every 1 (one) month. Suggestion Writer, It is expected to the Office of the Ministry of Justice and Human Rights Riau to prioritize and improve discipline, integrity and performance optimally in performing roles and functions in the implementation of supervision and repression of foreigners.Keywords: Role-Ministry of Justice and Human Rights-Immigration